ETNOMATEMATIKA PADA BUDAYA TIMOR (SUKU BOTI) DALAM PERSPEKTIF GEOMETRI - Samuel Igo Leton; Meryani Lakapu; Apridus K. Lapenangga; Wilfridus Beda Nuba Dosinaeng (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This research aimed to explore and explore the mathematical elements that grow and develop in the culture of the Boti tribe from a geometric perspective. The research design used was ethnography which consists of 6 stages, namely: selection of ethnographic objects, submission of ethnographic questions, data collection, data recording, data analysis, and writing of the final report. The research instruments used were interview guidelines and observation guidelines. The subjects in this research were Usif Boti as the main informant along with several family members who also acted as translators. The results of the research showed that ethnomathematics can be found in the lopo construction process, including: measuring side lengths using fathoms units, as well as determining the equal distance between the four commander's pillars and making a circular roof lopo using a special technique specially developed by the Boti people and has been passed down from generation to generation. Geometry concepts such as the properties and area of flat shapes are also integrated into the Lopo Boti shape.